Extraction of silica and alumina from coal fly ash for the synthesis of zeolites - Kamarudin R.A.; Matlob A.S.; Jubri Z.; Ramli Z. (2023)
This paper reports the extraction of soluble silicates and aluminates from coal fly ash using microwave irradiation from a domestic microwave oven. Fifteen experimental conditions for the extraction were obtained using Box-Behnken design through manipulation of three variables namely sodium hydroxide (NaOH) concentration, power level of microwave irradiation and exposure time; each variable has three values. The variables with their values were; NaOH concentration (2, 4 and 6 M), exposure time to microwave irradiation (1, 3.5 and 6 min) and power level of the irradiation (10, 50 and 100 Watts). Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) was used to study the amount of silicon and aluminium in the extracts. The extracted silicates and aluminates (after the molar ratio of SiO2 to Al2O 3 was adjusted to unity by adding aluminium foil) were further incubated at 95C for 72 hours. The products isolated from the 14 experiments were characterized by their XRD images and found to be Na-A zeolites, gibbsite and sodalite octahydrate. 2009 IEEE.